An updated parametric hysteretic model for steel tubular members considering compressive buckling. (December 2021) - Zhang, Yujian; Luo, Yongfeng; Guo, Xiaonong; Li, Yunsong
Abstract: An updated parametric hysteretic model for steel tubular members, in which the member compressive buckling is considered, is proposed in this paper. The model can be used for simulating the complex inelastic force-displacement hysteresis behaviour of steel tubular members. Based on the general aspects of hysteretic behaviour and the traditional Marshall model, the modified Marshall model is developed to improve the simulation accuracy, whose control parameters are determined by batch parameter analysis results. For the applicability in multiple hysteresis loop process, the initial member curvature under compression-tension during hysteretic loop process is studied and the computation methods under compression and tension are given individually based on the finite element analysis results and theoretical derivation. On this foundation, the model control parameter correction and axial compression capacity redefined with large initial member curvature during hysteretic loop process are executed in the updated parametric hysteretic model proposed later in this paper. Finally, in addition to the comparison with the finite element results, the rationality and applicability of the proposed model are also verified by several experiments and the good agreement in loop curve trend and hysteretic energy consumption are found between the simulated and experimental results. Graphical abstract: Unlabelled Image Highlights: The modified Marshall model is developed based on the parametric description of hysteretic behaviour. The model control parameter correction and axial compression capacity are redefined during hysteretic loop process. Comparing with other methods, remarkable improvement in accuracy is achieved by the proposed version.